Perlakuan Berbagai Dosis Pupuk ZA Pertumbuhan Dan Hasil Tanaman Bayam Merah (Amaranthus gangeticus) - Kustiani, Edy; Mariyono, Mariyono; Ayuningtyas, Bela Citra (Kadiri University, 2021)
Red spinach (Amaranthus gangeticus) is one of the most popular vegetables because of its high nutritional value and easy cultivation. Efforts to increase the production of red spinach are to fertilize to meet the needs of both macro and micronutrients. This study aimed to determine the effect of ZA fertilizer dose on the growth and yield of red spinach. The environmental design used was a non-factorial, completely randomized design with four replications. The factors tested were the dose of ZA fertilizer which consisted of 6 levels, namely: without ZA fertilizer (D0); 0.4 gr/polybag (D1); 0.8 gr/polybag (D2); 1.2 gr/polybag (D3); 1.6 gr/polybag (D4); 2 gr/polybag (D5). The data obtained were analyzed using analysis of variance, and if the results were significantly different, the BNT test was continued at a 5% level. The growth and yield of red spinach showed significant differences due to the ZA fertilizer dose treatment. The ZA fertilizer dose treatment of 1.2 g/polybag (D3) resulted in the highest plant height, the number of leaves, and leaf area of red spinach at 14, 21, and 28 days after planting. The ZA fertilizer dose treatment of 1.2 g/polybag (D3) resulted in the highest wet and dry weight plants of 49.15 and 4.38 grams, respectively. The ZA 1.2 gr/polybag dose is the ideal dose to increase the productivity of red spinach.Bayam merah (Amaranthus gangeticus) termasuk sayuran penting yang disukai masyarakat karena bernilai gizi tinggi dan mudah pembudidayaannya. Upaya peningkatan hasil bayam merah salah satunya dengan pemupukan untuk menambah nutrisi yang dibutuhkan tanaman. Tujuan dari penelitian ini adalah mempelajari respon pertumbuhan dan hasil tanaman bayam merah pada perlakuan dosis pupuk ZA. Pelaksanaan penelitian ini menggunakan Rancangan Acak Lengkap (RAL) satu faktor. Faktor yang diujikan adalah dosis pupuk ZA, terdiri 6 taraf, yaitu: tanpa pupuk ZA (D0); 0.4 gr/polybag (D1); 0.8 gr/polybag (D2); 1.2 gr/polybag (D3); 1.6 gr/polybag (D4); 2 gr /polybag (D5). Percobaan dilakukan dengan ulangan sebanyak 4 kali. Analisis data menggunakan analysis of variance (ANOVA), apabila berbeda nyata dilanjutkan uji Beda Nyata Terkecil (BNT) taraf 5%. Perlakuan dosis pupuk ZA berpengaruh nyata terhadap pertumbuhan dan hasil tanaman bayam merah. Perlakuan dosis pupuk ZA 1.2 gr/polybag (D3) menghasilkan tinggi, jumlah dan luas daun tanaman bayam merah tertinggi pada pengamatan umur 14, 21, dan 28 HST. Dosis pupuk ZA 1.2 gr/polybag (D3) juga menunjukkan berat basah dan berat kering tanaman tertinggi sebesar 49.15 dan 4.38 gram. Dosis ZA 1.2 gr/polybag merupakan dosis ideal untuk meningkatkan produktivitas tanaman bayam merah.